SISTEM PENGUKURAN KEKASARAN PERMUKAAN DINDING SUMUR BETON MENGGUNAKAN ULTRASONIC RANGING DENGAN MEDIA PENYIMPANAN DATA LOGGER - Vifaldi Agti; Suryono Suryono (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Research of the application of ultrasonics wave for measurements of level of surface roughness of wall of the well concrete have been done. This purpose of research is create sensor system and data acquisition ultrasonic ranging for measure surface roughness of wall of the well and create data logger system which can store measurement results. This method included in non destructive test because It’s used of secure wave spectrum region and nocontact measurement system. In this research, ultrasonic pulse generator using microcontroller ATSAM3X8E and the ultrasonic transducer is work on frequency of 40kHz. The transducer emits ultrasonic pulses to the object via the transmitter and receive back the wave reflection on the receiver. ultrasonic waves are transmitted through air media experience attenuation and reflected towards the object until received by the receiver. The object used as the measurement of roughness is wall of the well concrete, reasons for choosing this object is to minimize attenuation, thus increasing the reflection of ultrasonic waves. In the method of time-of-flight measurement is done by rotating transducer for scanning object using the DC motor. The measurement results is stored in a data logger using the SD Card. To get the surface roughness profile, the distance data obtained is calculated using standard deviation equation. Then obtained a deviation of the roughness profile, the lowest value is 0.255 cm, the highest score is 0.730 cm, and the average value is 0,495 cm.